Geology and features of volcanism on the Sea of Okhotsk floor. - Emelyanova, T A; Lelikov, Evgeny P; Sedin, V T; Naryzhnyy, V L (PANGAEA, 2003)
Volcanogenic rocks from the Sea of Okhotsk are divided into seven age complexes: Late Jurassic, Early Cretaceous, Late Cretaceous, Eocene, Late Oligocene, Late Miocene, and Pliocene-Pleistocene. All these complexes are united into two groups - Late Mesozoic and Cenozoic. Each group reflects a certain stage of development of the Sea of Okhotsk region. Late Mesozoic volcanites build the geological basement of the Sea of Okhotsk, and their petrochemical features are similar to those of the volcanic rocks from the Okhotsk-Chukotka Volcanogen. Pliocene-Pleistocene volcanites reflect stages of tectono-magmatic activity; the latter destroyed the continental margin and produced riftogenic troughs. Geochemical features of volcanites from the Sea of Okhotsk indicate influence of the sialic crust on magma formation and testify formation of the Okhotsk Sea Basin on the destructive margin of the Asian continent.
K-Ar age and chemical composition of volcanites from the Sea of Okhotsk
Keywords: Archive of Ocean Data; ARCOD; Dredge; DRG; LV27-14; LV27-19; Sea of Okhotsk; SOO03-2120; SOO03-2122; SOO03-2357; SOO03-3105; SOO03-3110; SOO03-3111; SOO03-3115; SOO03-3116; SOO03-3118; SOO03-3120; SOO03-3125; SOO03-3133; SOO03-3157; SOO03-4218